PARENTS’ INVOLVEMENT IN THE EDUCATION OF CHILDREN WITH ISLAM BASED ON IMAM AL-GHAZALI’S PERSPECTIVE - Noornajihan Jaafar (Universitas Muhammadiyah Surakarta, 2024)
Parental involvement in children's education is crucial in any cultural or religious context, including Islam. Education is highly valued in Islam, and parents are considered their children's primary educators and role models. Parents are responsible for imparting religious education to their children. Therefore, this study aims to explain the essential elements of Muslim parenting from the perspective of Al-Ghazali, explore the importance of parents’ involvement in educating Islam, and analyze the effect of the parents' participation on children. This study applied document analysis and interviews as data collection methods. Five parents were interviewed with open-ended questions. As a result, there are three critical elements in parenting, according to Al-Ghazali, namely knowledge acquisition, worshipping Allah, and relation and responsibility towards children. All the participants agree that parents’ involvement in nurturing Islamic education in children is significant besides only focusing on academic education. Some participants' opinions regarding the effect of parents’ involvement in educating Islamic teaching, namely curbing bad influences, good behaviour or akhlak, and clear guidelines for children. This finding potentially creates awareness and offers guidance to parents, encouraging them to enhance their efforts for the well-being of their children and families. It serves as a reminder that when individuals prioritize practising and preserving their faith, Allah, the Almighty, ensures the well-being of the family structure, leading to harmony within the broader community.